Preparation method of clearance type TiC nanotube coating on surface of titanium fibrofelt

Through anodizing and molten salt electrolysis, the TiO2 nanotubes on the surface of titanium fiber felt are converted into TiC nanotubes under low temperature conditions, solving the problems of high temperature and adhesives in traditional nanoTiC preparation, achieving high specific surface area and excellent conductivity The preparation of gap type TiC nanotubes is suitable for conductive support materials.

CN119121345APending Publication Date: 2024-12-13NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411262819.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The high preparation temperature of traditional nanoTiC and the need for adhesives leads to high surface area, no adhesives, and high loading nanoTiC low temperature synthesis is challenging, limiting its wide application as a conductive support material.

Method used

TiO2 nanotube array coating was prepared on the surface of titanium fiber felt by anodizing method, and converted it into a gap type TiC nanotube coating under low temperature conditions by molten salt electrolysis, which was directly connected to the surface of titanium fiber to avoid sticking. Use of conjugates.

Benefits of technology

The preparation of gap type TiC nanotubes with high specific surface area, no adhesive and excellent conductivity on the surface of titanium fiber felt is realized, which reduces the preparation temperature and time, improves the conductivity and load of the material, and is suitable for conductive support materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121345A_ABST
    Figure CN119121345A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an interstitial TiC nanotube coating on the surface of a titanium fibrofelt. The method comprises the following steps: 1, preparing a TiO2 nanotube array coating on the surface of the titanium fibrofelt by adopting an anodic oxidation method; secondly, impurities in the molten salt are removed through pre-electrolysis and pre-soaking of TiO2, and purified molten salt is obtained; and thirdly, purified fused salt is adopted, the TiO2 nanotube array coating on the surface of the titanium fiber felt is converted into a TiC nanotube coating through a fused salt electrolysis method, and the titanium fiber felt surface gap type TiC nanotube coating is obtained. According to the method, an anodic oxidation method and a fused salt electrolysis method are combined, so that the gap type TiC nanotube coating is directly and tightly connected to the surfaces of titanium fibers in the titanium fiber felt, and the gap type TiC nanotube coating and the titanium fiber felt with micron pores form a unique micro-nano composite structure; the preparation of the gap type TiC nanotube with high specific surface area, no adhesive and excellent conductivity on the surface of the titanium fibrofelt is realized under a low-temperature condition, and the preparation method has good application potential in the aspect of conductive support materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molten salt electrochemistry, and in particular relates to a method for preparing a gap-type TiC nanotube coating on the surface of a titanium fiber felt. Background Art

[0002] Titanium carbide (TiC) has good electrical conductivity (10 5 S cm -1 ), oxidation resistance, corrosion resistance and mechanical stability, and is one of the ideal active material support materials. It is widely used in energy storage and conversion fields such as supercapacitors (SCs), metal ion batteries (MIBs), fuel cells, and electrocatalysis. For example, TiC can relieve the stress caused by the volume change of electrode materials during the charge and discharge of metal ion batteries due to its extremely high hardness and mechanical stability, and improve the cycle life; and TiC's good conductivity can provide a support framework for high electron transfer for active materials and improve reaction activity. In addition, TiC can also anchor single-atom catalysts, which is conducive to maximizing the number of active sites and improving reaction stability.

[0003] However, due to the limitations of the thermodynamic and kinetic conditions of the carbon thermal reduction reaction, the traditional preparation temperature of nano-TiC is usually above 1200°C, or a long mechanically induced self-propagating reaction is required to ensure sufficient diffusion rate and reaction uniformity. In addition, TiC nanopowders require additional conductive current collectors and adhesives for assembly, which not only increases the weight of the material, but also affects the transmission of electrons from the current collector to nano-TiC. Moreover, high load conditions can also lead to problems such as TiC agglomeration and difficulty in diffusion of electrolyte solutions. Therefore, although TiC has excellent performance advantages, the low-temperature synthesis of nano-TiC with high surface area, no adhesive, and high loading is still challenging, which limits its wide application as a conductive support material. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a gap-type TiC nanotube coating on the surface of titanium fiber felt in view of the above-mentioned shortcomings of the prior art. The method combines anodization with molten salt electrolysis to prepare TiO 2 The nanotube array coating is converted into an interstitial TiC nanotube coating and is directly and tightly connected to the surface of the titanium fiber in the titanium fiber felt. The preparation of interstitial TiC nanotubes with high specific surface area, no adhesive, and excellent conductivity on the surface of the titanium fiber felt is achieved under low temperature conditions, solving the problem of high temperature and adhesive requirement for the preparation of traditional nano-TiC.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a gap-type TiC nanotube coating on the surface of titanium fiber felt, characterized in that the method comprises the following steps:

[0006] Step 1: Prepare TiO on the surface of titanium fiber felt by anodic oxidation 2 Nanotube array coating;

[0007] Step 2: Pre-electrolysis and pre-soaking of TiO 2 Remove impurities from molten salt to obtain purified molten salt;

[0008] Step 3: Using the purified molten salt obtained in step 2, the TiO 2 The nanotube array coating is transformed into a TiC nanotube coating, and a gap-type TiC nanotube coating on the surface of the titanium fiber felt is obtained.

[0009] The above-mentioned method for preparing a gap-type TiC nanotube coating on the surface of a titanium fiber felt is characterized in that the electrolyte used in the anodizing method in step 1 is diethylene glycol-0.3wt% NH 4 F-0.6wt%HF-6wt%H 2 O system, and the temperature of the anodizing method is 40°C, the voltage is 60V, and the time is 2h.

[0010] The above-mentioned method for preparing the interstitial TiC nanotube coating on the surface of titanium fiber felt is characterized in that the titanium fiber felt after anodization in step 1 is annealed at 450°C for 2h. The present invention uses the above-mentioned annealing process to anneal the amorphous TiO 2 Transformed into anatase type, while increasing TiO 2 The adhesion of the nanotube coating is improved by avoiding the annealing temperature being too low to achieve phase transition and effectively improve the bonding strength of the coating, and the temperature being too high to cause the TiO 2 The problem of nanotube sintering and nanostructure damage.

[0011] The above-mentioned method for preparing a gap-type TiC nanotube coating on the surface of a titanium fiber felt is characterized in that the pre-electrolysis and pre-immersion of TiO 2 The following steps are involved:

[0012] Step 201, using a graphite rod as an anode and a stainless steel rod as a cathode, applying a 3V DC voltage to the molten salt for pre-electrolysis for 12 hours to remove impurities in the molten salt;

[0013] Step 202: Use stainless steel mesh to wrap TiO 2 The powder is then placed in the molten salt pre-electrolyzed in step 201 and immersed for 30 minutes to reduce CaO impurities in the molten salt.

[0014] The present invention first removes impurities in the molten salt by pre-electrolysis, and then pre-immerses the TiO 2 Further reducing the CaO impurity in the molten salt makes the CaO impurity in the molten salt reduced to an extremely low level, which is not achievable with the current pre-electrolysis technology.

[0015] The above-mentioned method for preparing a gap-type TiC nanotube coating on the surface of titanium fiber felt is characterized in that the molten salt in step 2 is CaCl 2 -LiCl system, and CaCl 2 The molar ratio of TiC to LiCl is 1:1. The mixed molten salt system with this composition ratio ensures complete melting at 600°C in the molten salt electrolysis method, effectively promoting the rapid formation of TiC products and facilitating the realization of TiO 2 The nanostructure is kept stable during the transformation to TiC.

[0016] The above-mentioned method for preparing a gap-type TiC nanotube coating on the surface of a titanium fiber felt is characterized in that the temperature of the molten salt electrolysis method in step 3 is 600°C, the applied voltage is 3.2V, and a molar ratio of 0.1% to 0.2% of Li 2 CO 3 As a carbon source, the electrolysis time is 0.5h to 1.5h. By controlling the process parameters of the molten salt electrolysis method, TiO 2 The nanostructure is kept stable during the transformation to TiC.

[0017] The above-mentioned method for preparing a gap-type TiC nanotube coating on the surface of titanium fiber felt is characterized in that the TiC nanotubes of the gap-type TiC nanotube coating on the surface of the titanium fiber felt described in step 3 are surrounded and loaded on the surface of the titanium fiber, and the thickness of the TiC nanotube coating is 1μm to 2μm. The TiC nanotubes are surrounded and loaded on the surface of the titanium fiber to form a unique three-dimensional interconnected nano-micro composite network structure, avoiding the instability and unevenness that may be caused by the use of binders in a solid-solid state; at the same time, the prepared TiC nanotubes have a certain spacing and a rough surface, which provides sufficient space and bonding strength for the loading of functional active ingredients, and ensures the rapid adsorption-desorption and migration of ions on the surface.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The present invention firstly adopts an anodic oxidation method to prepare TiO on the surface of titanium fiber felt. 2The nanotube array coating is then converted into an interstitial TiC nanotube coating by molten salt electrolysis, so that the TiC nanotube coating is directly and tightly connected to the surface of the titanium fiber in the titanium fiber felt without the need for an adhesive, and forms a unique micro-nano composite structure with the titanium fiber felt with micron pores, thereby obtaining a huge specific surface area, which is beneficial to the infiltration of the electrolyte solution, has excellent conductivity, and is suitable for conductive support materials.

[0020] 2. The interstitial TiC nanotube coating in the present invention is directly connected to the surface of the titanium fiber, which is beneficial to the direct transmission of electrons from the titanium current collector to the TiC nanotube. At the same time, the hollow structure inside the TiC nanotube and the gap between the nanotubes provide sufficient space for the loading of functional active ingredients, thereby increasing the loading amount, and also provide a smooth channel for the diffusion of ions during the electrochemical reaction, thereby further improving the conductivity.

[0021] 3. Compared with the limitations of traditional TiC nanomaterials, which have high preparation temperature (>1200℃), long synthesis time and high cost, the preparation method of the present invention, which adopts anodization combined with molten salt electrolysis, can quickly (as short as 0.5h) prepare interstitial TiC nanotube coating at a relatively low temperature (600℃), and has the advantages of simple operation and low production cost.

[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in Example 1 of the present invention.

[0024] Figure 2 This is a scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in Example 2 of the present invention.

[0025] Figure 3 This is a scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in Example 3 of the present invention.

[0026] Figure 4 This is a scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in Example 4 of the present invention.

[0027] Figure 5 This is a scanning electron microscope image of the surface product of the titanium fiber felt prepared in Comparative Example 1 of the present invention.

[0028] Figure 6 This is a scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0029] Example 1

[0030] This embodiment includes the following steps:

[0031] Step 1: Ultrasonic cleaning of titanium fiber felt in ethanol solution, and then placing in HF:HNO 3 :H 2 O=1:1:4 solution for 1s, HF mass concentration is 40%, HNO 3 The mass concentration is 65%, removing the surface oxide film;

[0032] The anodic oxidation method was used, with the soaked titanium fiber felt as the anode and the platinum sheet as the cathode, in a diethylene glycol-0.3wt%NH 4 F-0.6wt%HF-6wt%H 2 O system electrolyte, 60V voltage was applied at 40℃ for 2h to prepare TiO on the surface of titanium fiber felt. 2 The nanotube array coating was then annealed at 450 °C for 2 h;

[0033] Step 2: Pre-electrolysis and pre-soaking of TiO 2 Removal of CaCl 2 -LiCl mixed with impurities in molten salt to obtain purified CaCl 2 -LiCl mixed molten salt; the pre-electrolysis and pre-soaking of TiO 2 The following steps are involved:

[0034] Step 201: CaCl 2 The molar ratio of CaCl to LiCl is 1:1 2 -LiCl mixed molten salt was added to the corundum crucible and placed in the electrolytic furnace. After evacuation, high-purity argon was continuously introduced to ensure a good inert atmosphere in the furnace. Then, CaCl 2 -LiCl mixed molten salt is heated to 600℃ and kept warm for 30min;

[0035] The graphite rod is used as the anode and the stainless steel rod is used as the cathode to heat the CaCl 2 -LiCl mixed molten salt was pre-electrolyzed for 12 h with a 3 V DC voltage to remove CaCl 2 - Impurities in LiCl mixed molten salt;

[0036] Step 202: Use stainless steel mesh to wrap 1g of TiO 2 The powder is then placed in the molten salt pre-electrolyzed in step 201 and immersed for 30 minutes to reduce CaO impurities in the molten salt;

[0037] Step 3: Using molten salt electrolysis, graphite is used as the anode, and the surface of the graphite with TiO 2The titanium fiber felt coated with nanotube arrays was used as cathode, and the purified CaCl obtained in step 2 2 -LiCl mixed molten salt is added with 0.1% Li 2 CO 3 As a carbon source, the TiO 2 The nanotube array coating is converted into a TiC nanotube coating. After completion, the cathode is slowly taken out and cooled. The cathode is then repeatedly cleaned with 0.5 mol / L dilute hydrochloric acid and deionized water to remove residual molten salt on the surface, and then ultrasonically cleaned in ethanol and vacuum dried to obtain a gap-type TiC nanotube coating on the titanium fiber felt surface.

[0038] Figure 1 This is a scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in this example. Figure 1 It can be seen that the TiC nanotubes of the interstitial TiC nanotube coating on the surface of the titanium fiber felt are uniformly loaded around the surface of the titanium fiber, and the thickness of the TiC nanotube coating is 1 μm to 2 μm.

[0039] Example 2

[0040] This embodiment includes the following steps:

[0041] Step 1: Ultrasonic cleaning of titanium fiber felt in ethanol solution, and then placing in HF:HNO 3 :H 2 O=1:1:4 solution for 1s, HF mass concentration is 40%, HNO 3 The mass concentration is 65%, removing the surface oxide film;

[0042] The anodic oxidation method was used, with the soaked titanium fiber felt as the anode and the platinum sheet as the cathode, in a diethylene glycol-0.3wt%NH 4 F-0.6wt%HF-6wt%H 2 O system electrolyte, 60V voltage was applied at 40℃ for 2h to prepare TiO on the surface of titanium fiber felt. 2 The nanotube array coating was then annealed at 450 °C for 2 h;

[0043] Step 2: Pre-electrolysis and pre-soaking of TiO 2 Removal of CaCl 2 -LiCl mixed with impurities in molten salt to obtain purified CaCl 2 -LiCl mixed molten salt; the pre-electrolysis and pre-soaking of TiO 2 The following steps are involved:

[0044] Step 201: CaCl2 The molar ratio of CaCl to LiCl is 1:1 2 -LiCl mixed molten salt was added to the corundum crucible and placed in the electrolytic furnace. After evacuation, high-purity argon was continuously introduced to ensure a good inert atmosphere in the furnace. Then, CaCl 2 -LiCl mixed molten salt is heated to 600℃ and kept warm for 30min;

[0045] The graphite rod is used as the anode and the stainless steel rod is used as the cathode to heat the CaCl 2 -LiCl mixed molten salt was pre-electrolyzed for 12 h with a 3 V DC voltage to remove CaCl 2 - Impurities in LiCl mixed molten salt;

[0046] Step 202: Use stainless steel mesh to wrap 1g of TiO 2 The powder is then placed in the molten salt pre-electrolyzed in step 201 and immersed for 30 minutes to reduce CaO impurities in the molten salt;

[0047] Step 3: Using molten salt electrolysis, graphite is used as the anode, and the surface of the graphite with TiO 2 The titanium fiber felt coated with nanotube arrays was used as cathode, and the purified CaCl obtained in step 2 2 -LiCl mixed molten salt is added with 0.1% Li 2 CO 3 As a carbon source, the TiO 2 The nanotube array coating is converted into a TiC nanotube coating. After completion, the cathode is slowly taken out and cooled. The cathode is then repeatedly cleaned with 0.5 mol / L dilute hydrochloric acid and deionized water to remove residual molten salt on the surface, and then ultrasonically cleaned in ethanol and vacuum dried to obtain a gap-type TiC nanotube coating on the titanium fiber felt surface.

[0048] Figure 2 This is a scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in this example. Figure 2 It can be seen that the TiC nanotubes of the interstitial TiC nanotube coating on the surface of the titanium fiber felt are uniformly loaded around the surface of the titanium fiber, and the thickness of the TiC nanotube coating is 1 μm to 2 μm.

[0049] Example 3

[0050] This embodiment includes the following steps:

[0051] Step 1: Ultrasonic cleaning of titanium fiber felt in ethanol solution, and then placing in HF:HNO 3 :H 2O=1:1:4 solution for 1s, HF mass concentration is 40%, HNO 3 The mass concentration is 65%, removing the surface oxide film;

[0052] The anodic oxidation method was used, with the soaked titanium fiber felt as the anode and the platinum sheet as the cathode, in a diethylene glycol-0.3wt%NH 4 F-0.6wt%HF-6wt%H 2 O system electrolyte, 60V voltage was applied at 40℃ for 2h to prepare TiO on the surface of titanium fiber felt. 2 The nanotube array coating was then annealed at 450 °C for 2 h;

[0053] Step 2: Pre-electrolysis and pre-soaking of TiO 2 Removal of CaCl 2 -LiCl mixed with impurities in molten salt to obtain purified CaCl 2 -LiCl mixed molten salt; the pre-electrolysis and pre-soaking of TiO 2 The following steps are involved:

[0054] Step 201: CaCl 2 The molar ratio of CaCl to LiCl is 1:1 2 -LiCl mixed molten salt was added to the corundum crucible and placed in the electrolytic furnace. After evacuation, high-purity argon was continuously introduced to ensure a good inert atmosphere in the furnace. Then, CaCl 2 -LiCl mixed molten salt is heated to 600℃ and kept warm for 30min;

[0055] The graphite rod is used as the anode and the stainless steel rod is used as the cathode to heat the CaCl 2 -LiCl mixed molten salt was pre-electrolyzed for 12 h with a 3 V DC voltage to remove CaCl 2 - Impurities in LiCl mixed molten salt;

[0056] Step 202: Use stainless steel mesh to wrap 1g of TiO 2 The powder is then placed in the molten salt pre-electrolyzed in step 201 and immersed for 30 minutes to reduce CaO impurities in the molten salt;

[0057] Step 3: Using molten salt electrolysis, graphite is used as the anode, and the surface of the graphite with TiO 2 The titanium fiber felt coated with nanotube arrays was used as cathode, and the purified CaCl obtained in step 2 2 -LiCl mixed molten salt is added with 0.1% Li 2 CO 3 As a carbon source, the TiO2 The nanotube array coating is converted into a TiC nanotube coating. After completion, the cathode is slowly taken out and cooled. The cathode is then repeatedly cleaned with 0.5 mol / L dilute hydrochloric acid and deionized water to remove residual molten salt on the surface, and then ultrasonically cleaned in ethanol and vacuum dried to obtain a gap-type TiC nanotube coating on the titanium fiber felt surface.

[0058] Figure 3 This is a scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in this example. Figure 3 It can be seen that the TiC nanotubes of the interstitial TiC nanotube coating on the surface of the titanium fiber felt are uniformly loaded around the surface of the titanium fiber, and the thickness of the TiC nanotube coating is 1 μm to 2 μm.

[0059] Example 4

[0060] This embodiment includes the following steps:

[0061] Step 1: Ultrasonic cleaning of titanium fiber felt in ethanol solution, and then placing in HF:HNO 3 :H 2 O=1:1:4 solution for 1s, HF mass concentration is 40%, HNO 3 The mass concentration is 65%, removing the surface oxide film;

[0062] The anodic oxidation method was used, with the soaked titanium fiber felt as the anode and the platinum sheet as the cathode, in a diethylene glycol-0.3wt%NH 4 F-0.6wt%HF-6wt%H 2 O system electrolyte, 60V voltage was applied at 40℃ for 2h to prepare TiO on the surface of titanium fiber felt. 2 The nanotube array coating was then annealed at 450 °C for 2 h;

[0063] Step 2: Pre-electrolysis and pre-soaking of TiO 2 Removal of CaCl 2 -LiCl mixed with impurities in molten salt to obtain purified CaCl 2 -LiCl mixed molten salt; the pre-electrolysis and pre-soaking of TiO 2 The following steps are involved:

[0064] Step 201: CaCl 2 The molar ratio of CaCl to LiCl is 1:1 2 -LiCl mixed molten salt was added to the corundum crucible and placed in the electrolytic furnace. After evacuation, high-purity argon was continuously introduced to ensure a good inert atmosphere in the furnace. Then, CaCl 2 -LiCl mixed molten salt is heated to 600℃ and kept warm for 30min;

[0065] The graphite rod is used as the anode and the stainless steel rod is used as the cathode to heat the CaCl 2 -LiCl mixed molten salt was pre-electrolyzed for 12 h with a 3 V DC voltage to remove CaCl 2 - Impurities in LiCl mixed molten salt;

[0066] Step 202: Use stainless steel mesh to wrap 1g of TiO 2 The powder is then placed in the molten salt pre-electrolyzed in step 201 and immersed for 30 minutes to reduce CaO impurities in the molten salt;

[0067] Step 3: Using molten salt electrolysis, graphite is used as the anode, and the surface of the graphite with TiO 2 The titanium fiber felt coated with nanotube arrays was used as cathode, and the purified CaCl obtained in step 2 2 -LiCl mixed molten salt is added with 0.2% Li 2 CO 3 As a carbon source, the TiO 2 The nanotube array coating is converted into a TiC nanotube coating. After completion, the cathode is slowly taken out and cooled. The cathode is then repeatedly cleaned with 0.5 mol / L dilute hydrochloric acid and deionized water to remove residual molten salt on the surface, and then ultrasonically cleaned in ethanol and vacuum dried to obtain a gap-type TiC nanotube coating on the titanium fiber felt surface.

[0068] Figure 4 This is a scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in this example. Figure 4 It can be seen that the TiC nanotubes of the interstitial TiC nanotube coating on the surface of the titanium fiber felt are uniformly loaded around the surface of the titanium fiber, and the thickness of the TiC nanotube coating is 1 μm to 2 μm.

[0069] Comparative Example 1

[0070] The difference between this comparative example 1 and example 2 is that the purification of CaCl in step 3 2 -LiCl mixed molten salt is added with Li 2 CO 3 As a carbon source.

[0071] Figure 5 The scanning electron microscope image of the surface product of the titanium fiber felt prepared in this comparative example is as follows: Figure 5 It can be seen that the products on the surface of the titanium fiber felt are sintered and agglomerated together, and the nano-morphology completely disappears.

[0072] Comparative Example 2

[0073] The difference between this comparative example 1 and example 2 is that the electrolysis time in step 3 is 10 min.

[0074] Figure 6 The scanning electron microscope image of the interstitial TiC nanotube coating on the surface of the titanium fiber felt prepared in this comparative example is shown in FIG. Figure 6 It can be seen that the morphology of the TiC nanotubes in the interstitial TiC nanotube coating on the surface of the titanium fiber felt is severely damaged.

[0075] Comparing Example 2 with Comparative Example 1, it can be seen that the additional carbon source Li 2 CO 3 Medium CO 3 2- The addition of promotes the formation of TiC, thereby increasing the TiO 2 Nanomorphological integrity during the transformation of nanotubes to TiC nanotubes.

[0076] Comparing Example 2 with Comparative Example 2, it can be seen that the shorter electrolysis time leads to a lower content of high-melting-point TiC in the product, and the product will be morphologically damaged during the cooling process at the end of electrolysis.

[0077] In summary, the present invention proposes a method for preparing a gap-type TiC nanotube coating on the surface of titanium fiber felt, which can realize the preparation of gap-type TiC nanotubes on the surface of titanium fiber felt at a relatively low temperature (600°C), and has the advantages of simple operation and low production cost. The TiC nanotube coating prepared by this method is directly connected to the surface of titanium fiber, and has the advantages of large specific surface area, no adhesive, high conductivity, etc., which is conducive to the direct transmission of electrons from the titanium current collector to the TiC material; at the same time, the hollow structure inside the TiC nanotube and the gap between the nanotubes can provide sufficient space for the loading of functional active materials, and can also provide a smooth channel for the diffusion of ions.

[0078] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a gap-type TiC nanotube coating on the surface of a titanium fiber felt, characterized in that: The method comprises the following steps: Step 1: preparing a TiO2 nanotube array coating on the surface of titanium fiber felt by an anodic oxidation method; Step 2: removing impurities in the molten salt by pre-electrolysis and pre-soaking TiO2 to obtain purified molten salt; Step three: using the purified molten salt obtained in step two, convert the TiO2 nanotube array coating on the surface of the titanium fiber felt in step one into a TiC nanotube coating by molten salt electrolysis to obtain a gap-type TiC nanotube coating on the surface of the titanium fiber felt.

2. The method for preparing a gap-type TiC nanotube coating on the surface of a titanium fiber felt according to claim 1, characterized in that: The electrolyte used in the anodization method in step 1 is a system of diethylene glycol-0.3wt% NH4F-0.6wt% HF-6wt% H2O, and the temperature of the anodization method is 40°C, the voltage is 60V, and the time is 2h.

3. The method for preparing a gap-type TiC nanotube coating on the surface of titanium fiber felt according to claim 1, characterized in that: The titanium fiber felt anodized in step 1 was annealed at 450° C. for 2 h.

4. The method for preparing a gap-type TiC nanotube coating on the surface of a titanium fiber felt according to claim 1, characterized in that: The pre-electrolysis and pre-soaking of TiO2 in step 2 comprises the following steps: Step 201, using a graphite rod as an anode and a stainless steel rod as a cathode, applying a 3V DC voltage to the molten salt for pre-electrolysis for 12 hours to remove impurities in the molten salt; Step 202: Wrap the TiO2 powder with a stainless steel mesh, and then soak it in the molten salt pre-electrolyzed in step 201 for 30 minutes to reduce CaO impurities in the molten salt.

5. The method for preparing a gap-type TiC nanotube coating on the surface of titanium fiber felt according to claim 1, characterized in that: The molten salt in step 2 is a CaCl2-LiCl system, and the molar ratio of CaCl2 to LiCl is 1:

1.

6. The method for preparing a gap-type TiC nanotube coating on the surface of titanium fiber felt according to claim 1, characterized in that: The temperature of the molten salt electrolysis method in step three is 600° C., the applied voltage is 3.2 V, and 0.1% to 0.2% of Li2CO3 is added to the purified molten salt as a carbon source, and the electrolysis time is 0.5h to 1.5h.

7. The method for preparing a gap-type TiC nanotube coating on the surface of titanium fiber felt according to claim 1, characterized in that: In step 3, the TiC nanotubes of the interstitial TiC nanotube coating on the surface of the titanium fiber felt are surrounded and loaded on the surface of the titanium fiber, and the thickness of the TiC nanotube coating is 1 μm to 2 μm.

Citation Information

Patent Citations

  • Preparation method of titanium dioxide nanotube-ruthenium-titanium oxide coating titanium electrode

    CN107740138A

  • TiC nanotube array material and preparation method and application thereof

    CN114388275A

  • Preparation method of gradient titanium-based boron-doped diamond film electrode

    CN117568776A

  • Titanium oxide nanohole structure and method of manufacturing the same

    JP2011047014A